2014
DOI: 10.3892/ijmm.2014.1715
|View full text |Cite
|
Sign up to set email alerts
|

The combination of rapamycin and MAPK inhibitors enhances the growth inhibitory effect on Nara-H cells

Abstract: The inhibition of the mammalian target of rapamycin (mTOR) signaling pathway promotes the initiation of autophagy, and the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated protein kinase (ERK) is well known to induce autophagy. Autophagy is a self-defense mechanism of cancer cells that are subjected to antitumor agents, and blocking autophagy can trigger apoptosis. In the present study, we demonstrate that an mTOR inhibitor, rapamycin, induces autophagy in the Nara-H malignant fibrous his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…To our knowledge this is the first report demonstrating the role of ERK in autophagy-mediated increase in PRR expression. Previous studies showed that rapamycin increased ERK phosphorylation at 24 h (5,27). Knockout of p62 in mice enhanced ERK activation (18).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To our knowledge this is the first report demonstrating the role of ERK in autophagy-mediated increase in PRR expression. Previous studies showed that rapamycin increased ERK phosphorylation at 24 h (5,27). Knockout of p62 in mice enhanced ERK activation (18).…”
Section: Discussionmentioning
confidence: 92%
“…P62, also known as sequestosome-1, is a protein that targets specific cargoes and is required for the formation and the degradation of autophagolysosomes by proteases. Inhibition of the V-AT-Pase by bafilomycin, and therefore blockade of the degradation of autophagolysosomal contents by lysosomal proteases, results in the accumulation of p62 (27). Thus, p62 can be used as a biomarker for the status of autophagic activity (4).…”
mentioning
confidence: 99%
“…Recently, it was shown that ERK activation could regulate expression levels of LC3B and SQSTM1/p62 [ 26 ]. ERK activity is also needed for autophagy in the Nara-H malignant fibrous histiocytoma cell line and in these cells rapamycin induces autophagy, through p-ERK, as well as apoptosis [ 27 ]. In these cells, upon UO126 treatment, apoptosis is enhanced, while autophagy is diminished.…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin, an mTOR inhibitor, is widely used in the experimental and clinical researches for anti-neoplastic drugs ( Nakamura et al, 2014 ; Wang et al, 2014 ). The mTOR inhibitors have been used in the clinical trial for several tumors, among them are rapamycin analogs temsirolimus and everolimus which have been used to treat some tumors ( Leung et al, 2011 ; Fasolo and Sessa, 2012 ; Voss et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%